ESG Disclosure and Firm Value the Moderating Role of Corporate Governance in Energy Sector Companies - Yonson Pane; Irvan Rolyesh Situmorang (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to investigate the effect of Environmental, Social, and Governance (ESG) disclosure on firm value, while examining the moderating role of corporate governance in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Design/methodology/approach – A quantitative research design was employed using secondary data collected from annual reports, sustainability reports, and corporate financial statements. The sample was determined through purposive sampling, focusing on energy sector firms consistently listed on the Indonesia Stock Exchange throughout the observation period. Data analysis was conducted using panel data regression with the assistance of EViews 13 software. Finding/Results – The empirical results reveal that ESG disclosure has a positive and significant effect on firm value. Furthermore, corporate governance, measured by the proportion of independent commissioners, was found to strengthen the relationship between ESG disclosure and firm value. These findings indicate that the effectiveness of ESG practices in enhancing corporate value becomes more substantial when supported by strong governance quality. Originality/Value – This study contributes empirical evidence regarding the association between ESG disclosure and firm value within Indonesia’s energy sector by incorporating corporate governance as a moderating variable. In addition, the findings extend the relevance of signaling theory and agency theory in explaining how ESG disclosure and governance mechanisms shape investor responses toward energy companies.